2016
DOI: 10.1038/srep18765
|View full text |Cite|
|
Sign up to set email alerts
|

Ionizing radiation modulates human macrophages towards a pro-inflammatory phenotype preserving their pro-invasive and pro-angiogenic capacities

Abstract: In order to improve the efficacy of conventional radiotherapy, attention has been paid to immune cells, which not only modulate cancer cell response to therapy but are also highly recruited to tumours after irradiation. Particularly, the effect of ionizing radiation on macrophages, using therapeutically relevant doses, is not well understood. To evaluate how radiotherapy affects macrophage behaviour and macrophage-mediated cancer cell activity, human monocyte derived-macrophages were subjected, for a week, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(121 citation statements)
references
References 63 publications
2
118
1
Order By: Relevance
“…The recruited heterogeneous populations of TAMs release proangiogenic cytokines and metalloproteinases to promote blood vessel formation within the tumor [19]. Teresa Pinto et al [20] also found that irradiated macrophages promote cancer cell invasiveness and cancer cell-induced angiogenesis. Besides, the abscopal effect may be a crucial factor in evaluation of the prognosis associated with radiotherapy, and TAMs can release secondary bystander signals and play a key role in the secondary bystander effect of photon irradiation [21].…”
Section: Tams Lead To a Poor Clinical Prognosis And Promote Progrementioning
confidence: 99%
“…The recruited heterogeneous populations of TAMs release proangiogenic cytokines and metalloproteinases to promote blood vessel formation within the tumor [19]. Teresa Pinto et al [20] also found that irradiated macrophages promote cancer cell invasiveness and cancer cell-induced angiogenesis. Besides, the abscopal effect may be a crucial factor in evaluation of the prognosis associated with radiotherapy, and TAMs can release secondary bystander signals and play a key role in the secondary bystander effect of photon irradiation [21].…”
Section: Tams Lead To a Poor Clinical Prognosis And Promote Progrementioning
confidence: 99%
“…Several pro‐inflammatory and immune‐related proteins with increased abundance were also identified, including CD163, Cathepsins, Myeloperoxidase, S100 Calcium Binding Proteins (Calprotectins), and HLA class II histocompatibility antigen DRα chain. These are strong indicators of macrophage and myeloid cell activation and function, potentially resulting from RT‐induced myeloid cell infiltration . Additionally, there was an overrepresentation of proteins strongly linked to serine protease activity—a well‐described functional element of the innate immune system in driving blood coagulation, inflammation, apoptosis and tissue remodeling .…”
Section: Discussionmentioning
confidence: 99%
“…Although their DNA was damaged upon irradiation, the macrophages remained viable and metabolically active and at 10 Gy cumulative dose a significant increase in pro-inflammatory macrophage markers CD80, CD86 and HLA-DR was observed, while anti-inflammatory markers CD163, MRC1, VCAN and IL-10 decreased. These results suggest that FIR facilitates the polarization of macrophages towards pro-inflammatory phenotype[40]. …”
Section: Macrophages Promote Lung Fibrosismentioning
confidence: 99%